The matchless amphibolite of the Damara Belt, Namibia: unique preservation of a Late Neoproterozoic ophiolitic suture - Meneghini, Francesca; Fagereng, Åke; Kisters, Alex (Ofioliti, 2017)
Ophiolitic sequences are widely recorded from Meso-Cenozoic orogenic belts, but are only rarely documented from Proterozoic-Paleozoic orogens, so that the geodynamic processes responsible for the emplacement of ancient ophiolites are less well understood compared to their younger counterparts. The Damara belt of Namibia represents a deeply eroded Pan-African (550-500 Ma) collisional belt that records subduction and the eventual collision between the Kalahari and Congo Cratons as part of the amalgamation of the Gondwana supercontinent. The belt has not been affected by later orogenic events so that it preserves the sequence of convergent and collisional tectonics remarkably well. The Southern Zone accretionary prism of the belt records the offscraping and imbrication of a thick metaturbiditic sequence. Within this sequence, the Matchless Amphibolite Belt forms a narrow, 500-3000 m wide unit of intrusive as well as imbricated mafic metavolcanic and plutonic rocks, with Mid-Ocean Ridge Basalt (MORB) geochemistry, that can be traced almost continuously for over 300 km along strike. Based on the MORB-type geochemistry and preserved textures and rock association, most authors consider the Matchless Amphibolite belt to represent relics of oceanic crust related to the closure of the oceanic basin between the Congo and Kalahari cratons. We have measured two traverses across the Matchless Amphibolite and we report here the evidence that these ophiolitic slivers emplaced during ridge-trench interaction and ridge subduction. We discuss factors that have most likely contributed to the formation and preservation of such an old ridge-trench encounter and its unique geometry